Clinico-pathological spectrum of testicular and paratesticular lesions: a retrospective study - Charak, Annu; Ahmed, Irfan; Sahaf, Bushra Rashid; Qadir, Rehana; Rather, A. R. (International Journal of Research in Medical Sciences, 2018)
Background: Both neoplastic and non neoplastic conditions affect the testis. Although non neoplastic testicular lesions are more common, still most of the studies were done on testicular neoplasms only. Hence the present study was undertaken to study histopathological spectrum of testicular and paratesticular lesions, their age distribution and clinical presentation. Methods: This is a retrospective study of 77 cases of orchidectomy specimens, testicular biopsies and paratesticular lesions received in the department from Jan 2015 to June 2018. Results: Non neoplastic testicular lesions were more common than neoplastic (90.1% Vs 9.8%) with majority in the second and third decade. Undescended testis comprised 46.1% of the total orchidectomy specimens followed by Torsion/Infarction testis (15.3%). None of the undescended testis showed tumour unlike western countries. Majority of patients presented with empty scrotum (31.16%) and testicular/scrotal swelling (18.11%). Only 5 cases of testicular neoplasm were diagnosed during the study period amounting to only 1.42 cases per year. All were germ cell tumours (4 classic seminoma and 1 yolk sac tumour). Conclusions: Non neoplastic testicular lesions were more common than neoplastic lesions. Complete neonatal examination for testicular descent should be mandatory to avoid late presentations and future malignancies. Germ cell tumours formed the bulk of testicular tumours.